2017
DOI: 10.2516/ogst/2017016
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Model Applied to the Barite Sag and Fluid Flow in Drilling Muds: Simulation and Experimental Results

Abstract: -In this work, a study on the modeling of sedimentation and transport of barite particles in drilling fluids was developed. The goal of this study was to evaluate the feasibility of using a simplified two-phase model based on conservation equations to describe the sedimentation of particulate material in drilling fluids. The model was evaluated in three different case studies, where the transport and the sedimentation of solid particles in a carrying fluid were simulated. The simulation results included a two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…where k e (t) is the equivalent filter cake permeability, mD; k 1 is the real situation with time-dependent filter cake permeability, mD; w o is the constant filter cake thickness, m; w(t) is the real situation with time-dependent filter cake thickness, m; and r w is the filter cake inner radius, m. During drilling, many factors such as drill-string rotational speed, annulus velocity, drilling fluid type, solid particle size, formation temperature, formation pressure, and formation permeability, can influence the time-dependent properties of the filter cake (Jaffal et al, 2018;Ma et al, 2020;Ribeiro et al, 2017;Veisi et al, 2020;Yao et al, 2014). Some experimental and mathematical models have been conducted to study the filter cake growth process (Fisher et al, 2000;Hashemzadeh and Hajidavalloo, 2016;Jaffal et al, 2017;Ma et al, 2020;Rabbani and Salehi, 2017), and their results showed that both the thickness and permeability of filter cake obey the exponential changing modes.…”
Section: Equivalent Filter Cake Permeabilitymentioning
confidence: 99%
“…where k e (t) is the equivalent filter cake permeability, mD; k 1 is the real situation with time-dependent filter cake permeability, mD; w o is the constant filter cake thickness, m; w(t) is the real situation with time-dependent filter cake thickness, m; and r w is the filter cake inner radius, m. During drilling, many factors such as drill-string rotational speed, annulus velocity, drilling fluid type, solid particle size, formation temperature, formation pressure, and formation permeability, can influence the time-dependent properties of the filter cake (Jaffal et al, 2018;Ma et al, 2020;Ribeiro et al, 2017;Veisi et al, 2020;Yao et al, 2014). Some experimental and mathematical models have been conducted to study the filter cake growth process (Fisher et al, 2000;Hashemzadeh and Hajidavalloo, 2016;Jaffal et al, 2017;Ma et al, 2020;Rabbani and Salehi, 2017), and their results showed that both the thickness and permeability of filter cake obey the exponential changing modes.…”
Section: Equivalent Filter Cake Permeabilitymentioning
confidence: 99%